THE ROLE OF BRAND IMAGE, PROMOTION, AND PRICE IN SHAPING PURCHASE INTEREST IN FLOWER BOUQUET PRODUCTS AT CV LAA TAHZAN FLORIST - Wulandari, Nanda; Muhammad Wadud (Jurnal Ilmu Manajemen (JIMMU), 2024)
This study aims to analyze the influence of brand image, promotion, and price on purchase intention of flower bouquet products at CV Laa Tahzan Florist. This research adopts a quantitative approach with a descriptive-associative design. The sample consists of 287 respondents selected using a purposive sampling technique through online questionnaire distribution. The data were analyzed using multiple linear regression. The results indicate that both partially and simultaneously, brand image, promotion, and price have a positive and significant effect on consumers' purchase intention. These findings highlight that the three variables are key determinants in shaping consumers’ decision to purchase flower bouquet products. The practical implication of this study is the importance for the company to strengthen its brand image, enhance promotional effectiveness, and apply competitive pricing strategies to attract consumer interest and expand market share.